THE INFLUENCE OF INFORMATION TECHNOLOGY USAGE ON THE EFFICIENCY AND EFFECTIVENESS OF ACCOUNTING INFORMATION SYSTEMS AND ITS IMPACT ON INVESTMENT DECISIONS: A SURVEY STUDY - Ali T.M. Kadawi; Khamoussi Halioui (American Journals, 2023)
The study aimed, on its theoretical side, to explain the impact of using information technology with its various multiple techniques on the efficiency and effectiveness of accounting information systems and how it reflects on investment decisions. This was achieved through reviewing the most important previous studies related to the research topic. Additionally, the study reviewed the significant technological innovations resulting from the Fourth Industrial Revolution. Regarding the practical aspect of the study, a questionnaire was formulated, consisting of two main axes, each containing five questions. The study's sample consisted of academic professionals working in the faculties of management and economics at Iraqi universities, specializing in accounting and finance. The study's results revealed positive and statistically significant differences in the use of information technology techniques on the efficiency and effectiveness of accounting information systems, with a positive impact on improving investment decision-making.
Keywords: Accounting Information System, Information Technology, Investment Decision